Impact of rotavirus vaccination on coverage and timing of pentavalent vaccination – Experience from 2 Latin American countries. Issue 5 (3rd May 2016) - Schweitzer, A.; Pessler, F.; Akmatov, M. K.
ABSTRACT: We examined the coverage and timing of rotavirus vaccination and the impact of rotavirus vaccine introduction on coverage and timing of the pentavalent vaccine. We used data from the Demographic and Health Surveys in Honduras (2011/2012) and Peru (2012). The samples were divided into 2 subcohorts: children born before and after the introduction of rotavirus vaccine. We compared coverage and timing of the pentavalent vaccine in the aforementioned subcohorts. Coverage with the first and second doses of rotavirus vaccination was 95% (95% confidence intervals: 93–97%) and 91% (89–95%) in Honduras and 79% (77–82%) and 72% (69–75%) in Peru, respectively. Coverage increased in both countries over the years. The proportion of children vaccinated according to age-appropriate vaccination schedules varied between 67% (second dose of rotavirus vaccinations in Peru) and 89% (first dose of rotavirus vaccination in Honduras). Coverage with the first and second doses of pentavalent vaccination remained constant over the years in Honduras, while in Peru there was a significant increase in coverage over the years (p for trend, <0.0001). In both countries, timing of pentavalent vaccination was better in post-rota-cohorts than in pre-rota-cohorts. Since its introduction, coverage of rotavirus vaccination has improved over time in both countries. An introduction of rotavirus vaccination in both countries appears to have improved the coverage and timing of other similarly scheduled vaccinations.